Peran Bedaquiline dan Penggunaannya pada Tuberkulosis Resisten Obat : Sebuah Kajian Naratif - Fiddina, Nisriyati; Yulistiani, Yulistiani (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2023)
Tuberculosis, caused by infection with Mycobacterium tuberculosis, is still a global concern. The existence of resistance to the first line of anti-TB, namely isoniazid and rifampicin, is an urgent need for the development of new drugs that are effective and safe against tuberculosis. Bedaquiline has received approval from the FDA as a new anti-TB drug discovered to treat drug-resistant tuberculosis. This article aims to review the role of bedaquiline in the treatment of drug-resistant tuberculosis mechanisms, evidence, effectiveness, and adverse events. This narrative review uses a literature study approach by identifying various literature and research articles through databases as relevant references. Bedaquililine belongs to the diarylquinoline class inhibits ATP-synthase activity and suppresses the growth of active and dormant mycobacteria. Various clinical trials conducted previously have evaluated the use of bedaquiline-based regimens for the treatment of adults with drug-resistant tuberculosis. Bedaquiline-based regimens showed efficacy and were generally well tolerated in numerous studies. Currently, further evaluation is needed regarding its efficacy, safety, and tolerability in drug-resistant tuberculosis patients in Indonesia.